Variational thinking mediated with algebraic tiles and virtual manipulators - Ordóñez-Ortega, Odair; Gualdrón-Pinto, Elgar; Amaya-Franky, Germán (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is the result of a type of action research with a qualitative approach that was developed with eighth grade students of Basic Education (13-15 years old). The purpose was to improve the variational thinking skills in the students chosen as a focus group. A diagnostic test was applied to evaluate the students' performance in the variational and geometric thinking. Based on the results, the group was intervened with a didactic unit, designed under a constructivist approach, using specific material and virtual manipulators. During the process it was observed that the implemented strategies motivated the students to achieve the objectives proposed by this study, even though initially the students did not feel sure of what they were doing because of the lack of experience in the use of specific instructional materials; however, there was evidence of improvements in the development of variational thinking, which suggests that in the topics of the current course and the following, students will have a better performance.